2008
DOI: 10.1139/z08-104
|View full text |Cite
|
Sign up to set email alerts
|

Nest-site characteristics and breeding success of three species of boreal songbirds in western Newfoundland, Canada

Abstract: Delineating habitat requirements and preferences of species is essential for conservation planning. We studied nest habitat use and effects of microsite vegetation characteristics on breeding success of yellow-rumped warblers ( Dendroica coronata (L., 1766)), blackpoll warblers ( Dendroica striata (J.R. Forster, 1772)), and white-throated sparrows ( Zonotrichia albicollis (Gmelin, 1789)) in an area with a low extent (<6% of available land) of forest harvest in northwestern Newfoundland. During 2004 and 2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Likewise, bed site selection of most ungulates with hiding young (sensu Lent 1974) is strongly influenced by predation risk (Caro 2005), although young ungulates might only do the best of a bad job because their survival is more strongly influenced by the availability of good bed sites within the maternal home range rather than by the young's selection among available bed sites (Van Moorter et al 2009). Likewise, songbirds (Dendroica coronate, Dendroica striata and Zonotrichia albicollis) did not enjoy any fitness benefit of nest site selection despite a clear association between nest site characteristics and nest success (Dalley et al 2008), and sage grouse (Centrocercus urophasianus) did not always select for nesting habitats that enhance chick survival (Aldridge & Boyce 2008). For conservation or management purposes, one should strive to enhance habitats that increase average individual fitness, and thereby population growth rate, rather than only habitats selected by animals.…”
Section: Measuring Individual Performance In Hprmentioning
confidence: 99%
“…Likewise, bed site selection of most ungulates with hiding young (sensu Lent 1974) is strongly influenced by predation risk (Caro 2005), although young ungulates might only do the best of a bad job because their survival is more strongly influenced by the availability of good bed sites within the maternal home range rather than by the young's selection among available bed sites (Van Moorter et al 2009). Likewise, songbirds (Dendroica coronate, Dendroica striata and Zonotrichia albicollis) did not enjoy any fitness benefit of nest site selection despite a clear association between nest site characteristics and nest success (Dalley et al 2008), and sage grouse (Centrocercus urophasianus) did not always select for nesting habitats that enhance chick survival (Aldridge & Boyce 2008). For conservation or management purposes, one should strive to enhance habitats that increase average individual fitness, and thereby population growth rate, rather than only habitats selected by animals.…”
Section: Measuring Individual Performance In Hprmentioning
confidence: 99%
“…Several authors have also found no association between nest success and nest-placement characteristics in other passerine species, attributing this to a number of causes, including very high predation, due to a diversity of predators, not avoidable by breeding-site selection, or previous occupation of microhabitats with comparatively lower predation risk which outweighs later analyses. 18,24,25,63 In contrast, in some scenarios where less favourable microhabitats are occupied, nesting success may be associated with nest-site features. 25 In the study area, overall bullfinch nesting success was low, slightly higher than 35% of nests, mainly due to the effect of a rich community of proven and potential predators.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the best response offered to date is a very small number of studies on limited numbers of species (e.g. [3] , [4] , [6] , [9] ) or those yielding relative indices of nesting success [13] , [15] [17] , [69] . The method proposed here is a potentially simple, effective and reliable tool for the assessment of parental status in a variety of environments.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of birds, nesting success is typically measured through nest monitoring [1]. Nest monitoring delivers a direct and reliable estimation of parameters such as nest survival [2], and the presence of nestlings [3] and fledglings [4]. Some studies have monitored a large number of nests [3], [5], sometimes for a large sampling area and a high number of bird species [5], [6].…”
Section: Introductionmentioning
confidence: 99%